Evolution of overweight and obesity among 5–6-year-old schoolchildren in Geneva (Swiss Medical Weekly, 2010)
Questions under study: In view of the alarming trend in childhood obesity (O) and overweight (OW) observed in certain countries, the aim of the study is to measure the prevalence of O and OW in successive cohorts of elementary school children in Geneva. Methods: All 5–6-year-old children attending public schools in the Canton of Geneva were measured and weighed during a systematic health check at school from 2003 to 2008. BMI was calculated and plotted on standardised BMI for age tables, using Cole’s and Kromeyer’s references. Results: Using Cole’s references, the overall trend was a small non-significant decrease for OW 0.7 points (p = 0.33) and O 0.5 points (p = 0.23) over the 5-year period. For girls, OW decreased by 1.1 point (p = 0.47) and O decreased by 0.5 points (p = 0.61), whilst for boys OW decreased by 0.3 points (p = 0.54) and O decreased by 0.6 points (p = 0.23). A non-significant decrease or stabilisation in the prevalence of overweight and obesity was observed over the 5-year period in both boys and girls. Conclusion: These observations corroborate observations from Sweden and France, showing a levelling off in obesity and overweight in young children.